Hak dan Kewajiban Keluarga Inti dalam Sistem Hukum Positif Indonesia (Perspektif Hukum Keluarga dan Perlindungan Hukum) - Gunawan, Bambang Indra; fitri_yani; Kartika, Fani Budi; Ihsan, Muhammad; Damayanti, Erni; Siagian, Tiopan (Publikasi Pengabdian Masyarakat, 2022)
The survival of the nation and state to build a civilization is to build a good quality family, then when a family has become good then the state will be good and quality so that Indonesian civilization can be built, then human resources become a central point that needs to be fostered and developed and One of the best places for HR education is in the family environment. One of the efforts to develop the potential of human resources so that they are able to ensure the survival of the nation and state can be done through education to understand the law to know the rights and obligations that have been determined by the state in building a good family so that they are able to also understand and provide legal protection for the components of the nuclear family who have accommodated in the legal system in Indonesia. So because of this, the state needs to be present in addition to creating law, the state must also conduct legal education socialization related to family law and legal protection for the community component, namely the nuclear family.